Wisdom texts from Qumran - Harrington, Daniel J. (Literature of the Dead Sea scrolls, 1996)
This study is the first full analysis of the Qumran wisdom texts. New translations and a full explanation of the background and context of wisdom literature introduce the reader to an important and hitherto little discussed part of the Dead Sea Scrolls.After surveying biblical and extrabiblical wisdom books, the author considers the best and most fully preserved wisdom texts from Qumran. The centrepiece of the book is a discussion of the large wisdom instruction known as Sapiential Work A. Also, the author reflects on the relevance of those texts for the study of early Judaism and Christia
Keywords: Dead Sea scrolls : Criticism, interpretation, etc; Wisdom literature : Criticism, interpretation, etc; Wisdom : Religious aspects : Judaism